Estudio de factibilidad para la creación de una productora y comercializadora de bolsos en cuero hechos a mano en la ciudad de Armenia Quindío. (2015)
The project presented below values the idea of a company creation that produces and markets handmade leather handbags. The initiative is considered based on the dynamics of the leather goods sector in Quindío, which in recent years has represented an alternative for employment in the craftsmanship area. In order to achieve the execution of the feasibility study, socioeconomic department information was collected. Also some instruments such as surveys and interviews with stakeholders were applied as the main input of market research with the purpose of identifying the supply and demand of bags in the different municipalities in Quindío Department. Technical and engineering components are addressed to determine the required conditions to keep in mind when starting the leather production. Moreover, the organizational structure of the company is designed by considering the regulations and environmental legislation. Finally the financial analysis indicates that the project is feasible , since the internal rate of return IRR 21.52 % is higher than the rate of 16.42% TIO Prospect. As a conclusion, the data collected and analyzed, regarding the feasibility to create the company is tangible due to the acceptance of potential customers towards the craft handbags. The region provides excellent availability of raw materials and inputs, and there is also a favorable environment which fosters the development of leather chain in the region, on account of the state- university-industry partnerships that will contribute to the preservation of traditional coffee production in the region , which is an attractive and important feature for the national tourism industry .